Street food and child labor: reality on the beaches of Salvador, Bahia, Brazil - Permínio Oliveira Vidal Júnior; Ryzia de Cassia Vieira Cardoso; José Ângelo Wenceslau Góes; Ícaro Ribeiro Cazumbá da Silva; Tássia Farias Santos Vianna; Isadora Soares Paiva; Daniela Maria Libório Fernandes; Hortência Fernandes Macedo (Fundação Oswaldo Cruz (FIOCRUZ), 2017)
The objective of this study was to describe the reality of children and teenagers working as street food vendors on the beaches of Salvador, and to uncover the social, economic, and sanitary aspects of their work. This cross-sectional study administered semi-structured questionnaires to 275 street food vendors under the age of 18 working on 18 city beaches. Participants' ages ranged from 5 to 17 years old, with a mean age of 13 years. Most vendors were males (71.3%), and 94.9% attended school. The most popular foods sold were queijo coalho, acarajé, and hard-boiled quail eggs. Most vendors had poor personal hygiene, although they considered hygiene important and recognized that street foods can cause disease. Some vendors (44.7%) cleaned the utensils daily. Few vendors (13.8%) admitted they did not wash their hands, and the remainder claimed to wash their hands two to five times a day with water or seawater, but this practice was not observed in the field. The results of this study confirm the presence of child and adolescent labor in the street food informal labor sector and substantiates the risk of street foods to consumers' health due to vendors' ignorance of hygiene principles.